2017
DOI: 10.1128/aac.00115-17
|View full text |Cite
|
Sign up to set email alerts
|

Terbinafine Resistance of Trichophyton Clinical Isolates Caused by Specific Point Mutations in the Squalene Epoxidase Gene

Abstract: Terbinafine is one of the allylamine antifungal agents whose target is squalene epoxidase (SQLE). This agent has been extensively used in the therapy of dermatophyte infections. The incidence of patients with tinea pedis or unguium tolerant to terbinafine treatment prompted us to screen the terbinafine resistance of all Trichophyton clinical isolates from the laboratory of the Centre Hospitalier Universitaire Vaudois collected over a 3-year period and to identify their mechanism of resistance. Among 2,056 test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
298
3
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 254 publications
(323 citation statements)
references
References 37 publications
10
298
3
12
Order By: Relevance
“…Trichophyton rubrum isolated from human dermatophytosis was reported to exhibit TRF resistance . Resistance of dermatophytes to antifungal drugs frequently results from overexpression of genes encoding ATP‐binding cassette (ABC) transporter proteins, including the pleiotropic drug resistance ( PDR1 ) and multidrug resistance ( MDR2 and MDR4 ) genes .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Trichophyton rubrum isolated from human dermatophytosis was reported to exhibit TRF resistance . Resistance of dermatophytes to antifungal drugs frequently results from overexpression of genes encoding ATP‐binding cassette (ABC) transporter proteins, including the pleiotropic drug resistance ( PDR1 ) and multidrug resistance ( MDR2 and MDR4 ) genes .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in recent work, Yamada et al . reported that a TRF‐resistant T. interdigitale strain (TIMM20096; TRF MIC, 3.2 mg/L) harbored missense mutations (Phe397Leu) in the SQLE ‐encoding gene.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations